Training for computerisation of library and information services - Rangra, V.K. (DESIDOC Journal of Library & Information Technology, 2002)
The dictionary meaning of training is to bring a person to desired state of standard of efficiency by instructions and practice .The main aim of training is to impact a specific skill which the recipient is expected to practice. Education on the other hand, seeks to bring out and develop the innate qualities of a person or to enhance his general reasoning power. Whereas training focuses attention to meet the present job requirements of the individual, education prepares him for a future but not for a defined job. Training cannot be taken as an isolated activity but is considered as a development process by which a person applies his training skills for improving his job performance and increasing organisational effectiveness.